SIMPLE AND RAPID METHOD FOR THE SIMULTANEOUS ANALYSIS OF TAMOXIFEN, ENDOXIFEN, AND 4-HYDROXYTAMOXIFEN IN DRIED BLOOD SPOT USING LIQUID CHROMATOGRAPHY–TANDEM MASS SPECTROMETRY - MAGGADANI, BAITHA PALANGGATAN; HARAHAP, YAHDIANA; HARMITA; HARYONO, SAMUEL J.; SITORUS, TESANIKA RIBKA JOULIN (International Journal of Applied Pharmaceutics, 2020)
Objective: Tamoxifen (TAM) is a hormonal therapy that is clinically proven to reduce breast cancer recurrence by blocking estrogen receptor, mainly through its active metabolites, 4-hydroxytamoxifen (4HT) and endoxifen (END), which have a higher affinity to ER than TAM itself. The objective of the present study was to develop and validate simple and rapid LC-MS/MS method for analysis TAM and its metabolites simultaneously in dried blood spot (DBS) sample for monitoring studies purposes. Methods: Optimization was done by evaluating several parameters that affect the efficiency of DBS preparation, such as blood spot volume, drying time and extraction method from the DBS paper. The effectiveness of chromatographic conditions was also optimized by varying flow rate, mobile phase combination and gradient. Clomiphene was used as the internal standard. Results: The result showed that preparation of 20 µl blood spot volume with 120 min of drying time and 25 min of extraction time using 1 ml methanol was the most efficient condition and also fulfilled recovery and matrix effect requirement according to FDA and EMA guidelines. The separation was performed on UPLC Class BEH C18 using formic acid 0.1%-formic acid 0.1% in acetonitrile (35:65) as the mobile phase in isocratic mode at 0.25 ml/min with a total analysis time of 4 min. Conclusion: This method has successfully fulfilled all validation requirements referring to EMA and FDA guidelines.